Pharmacokinetics and Pharmacodynamics of Florfenicol in Plasma and Synovial Fluid of Pigs at a Dose of 30 mg/kgbw Following Intramuscular Administration - Zoltán Somogyi; Patrik Mag; Réka Simon; Ádám Kerek; Pál Szabó; Ervin Albert; Imre Biksi; Ákos Jerzsele (MDPI AG, 2023)
A major problem of our time is the ever-increasing resistance to antimicrobial agents in bacterial populations. One of the most effective ways to prevent these problems is to target antibacterial therapies for specific diseases. In this study, we investigated the in vitro effectiveness of florfenicol against S. suis, which can cause severe arthritis and septicemia in swine herds. The pharmacokinetic and pharmacodynamic properties of florfenicol in porcine plasma and synovial fluid were determined. After a single intramuscular administration of florfenicol at 30 mg/kgbw, the AUC0-∞ was 164.45 ± 34.18 µg/mL × h and the maximum plasma concentration was 8.15 ± 3.11 µg/mL, which was reached in 1.40 ± 0.66 h, whereas, in the synovial fluid, these values were 64.57 ± 30.37 µg/mL × h, 4.51 ± 1.16 µg/mL and 1.75 ± 1.16 h, respectively. Based on the MIC values of the 73 S. suis isolates tested, the MIC50 and MIC90 values were 2 µg/mL and 8 µg/mL, respectively. We successfully implemented a killing-time curve in pig synovial fluid as a matrix. Based on our findings, the PK/PD breakpoints of the bacteriostatic (E = 0), bactericidal (E = −3) and eradication (E = −4) effects of florfenicol were determined and MIC thresholds were calculated, which are the guiding indicators for the treatment of these diseases. The AUC24h/MIC values for bacteriostatic, bactericidal and eradication effects were 22.22 h, 76.88 h and 141.74 h, respectively, in synovial fluid, and 22.42 h, 86.49 h and 161.76 h, respectively, in plasma. The critical MIC values of florfenicol against S. suis regarding bacteriostatic, bactericidal and eradication effects in pig synovial fluid were 2.91 ± 1.37 µg/mL, 0.84 ± 0.39 µg/mL and 0.46 ± 0.21 µg/mL, respectively. These values provide a basis for further studies on the use of florfenicol. Furthermore, our research highlights the importance of investigating the pharmacokinetic properties of antibacterial agents at the site of infection and the pharmacodynamic properties of these agents against different bacteria in different media.